The importance and impact of public engagement for the nuclear industry - Hutson, C; Martin, P; Payne, L; Logan, M; Dong, L (WM Symposia, 2017)
The South West Nuclear Hub has joined with its industrial partners to engage with the public about the pros and cons of nuclear power, and open a balanced and evidence-based dialogue around common areas of concern, such as nuclear safety and nuclear waste. This programme of industrial engagement must continue into the future if we are to understand and effectively address those concerns, and make the UK’s nuclear renaissance work for all.